John Scofield on improvisation - Scofield, John.; DCI Music Video (New York, N.Y. : DCI Music Video, 1983)
Scofield, a guitarist, discusses and demonstrates technique of improvisation: use of major modes and scales, chromatics, passing tones, melodic devices and rhythm; also picking techniques and equipment.
VHS format.
Keywords: Guitar -- Instruction and study; Improvisation (Music); Jazz musicians -- Interviews